2021
DOI: 10.1136/bmjopen-2020-048592
|View full text |Cite
|
Sign up to set email alerts
|

Mortality trends and access to care for cardiovascular diseases in Agincourt, rural South Africa: a mixed-methods analysis of verbal autopsy data

Abstract: ObjectivesCardiovascular diseases are the second leading cause of mortality behind HIV/AIDS in South Africa. This study investigates cardiovascular disease mortality trends in rural South Africa over 20+ years and the associated barriers to accessing care, using verbal autopsy data.DesignA mixed-methods approach was used, combining descriptive analysis of mortality rates over time, by condition, sex and age group, quantitative analysis of circumstances of mortality (CoM) indicators and free text narratives of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“… 60 More than three quarters of the studies (32/42) were surveillance studies. 19 , 21 24 , 26 , 28 44 , 48 52 , 54 , 55 , 57 , 58 Of 39 studies that recorded the study setting, 19 39 , 41 55 , 57 , 59 , 60 18 covered rural populations, 26 , 28 , 30 , 32 , 34 , 35 , 37 , 39 , 41 44 , 48 50 , 52 , 53 , 55 six covered urban populations, 21 , 25 , 46 , 47 , 51 , 59 and 15 covered both rural and urban populations at the country level. 19 , 20 , 22 24 , 27 , 29 , 31 , 33 , 36 , 38 , 45 , 54 , 57 , 60 The number of verbal autopsy deaths reported across all ages ranged between studies from 515 to 22 535, 47 , 53 and 20 studies reported deaths by sex.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 60 More than three quarters of the studies (32/42) were surveillance studies. 19 , 21 24 , 26 , 28 44 , 48 52 , 54 , 55 , 57 , 58 Of 39 studies that recorded the study setting, 19 39 , 41 55 , 57 , 59 , 60 18 covered rural populations, 26 , 28 , 30 , 32 , 34 , 35 , 37 , 39 , 41 44 , 48 50 , 52 , 53 , 55 six covered urban populations, 21 , 25 , 46 , 47 , 51 , 59 and 15 covered both rural and urban populations at the country level. 19 , 20 , 22 24 , 27 , 29 , 31 , 33 , 36 , 38 , 45 , 54 , 57 , 60 The number of verbal autopsy deaths reported across all ages ranged between studies from 515 to 22 535, 47 , 53 and 20 studies reported deaths by sex.…”
Section: Resultsmentioning
confidence: 99%
“… 20 , 36 , 59 In just over half the studies (22/42), the cause of death was ascertained by physicians; 22 , 24 , 27 31 , 33 , 36 38 , 40 , 41 , 43 , 45 , 49 52 , 54 56 , 60 in 15 studies, cardiovascular disease deaths were ascertained using InterVA (Umeå Centre for Global Health Research, Umeå, Sweden) or SmartVA (Institute for Health Metrics and Evaluation, Seattle, USA) software. 19 , 21 , 23 , 25 , 26 , 32 , 34 , 35 , 39 , 42 , 44 , 48 , 53 , 57 , 58 …”
Section: Resultsmentioning
confidence: 99%